2020
DOI: 10.1002/wwp2.12038
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the dams on water and plankton quality of the River Ganga (Gangotri to Vindhyachal)

Abstract: The river Ganga originates from Gangotri and travels approximate 1,300 km to Vindhyachal, bypassing through a series of dams. Water quality parameters including temperature, pH, dissolved oxygen, alkalinity, chloride, biological oxygen demand, dissolved organic matter, and nutrients were studied from various centers of the river Ganga from Gangotri to Vindhyachal (24 centers). Specific conductivity increased gradually from Maneri above barrage area and reached maximum at Kanpur as the river receives industrial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
1
0
Order By: Relevance
“…Khanna et al [9] reported a total absence of rotifers during the monsoon season in the Ganga River, as seen in the present study at site A2. Welch [27,28,29] among others, have also reported a similar trend. The maximum density of 4844 Individuals/L in Ganga River at the site in January, a similar trend was observed by Magar [30].…”
Section: Resultssupporting
confidence: 60%
“…Khanna et al [9] reported a total absence of rotifers during the monsoon season in the Ganga River, as seen in the present study at site A2. Welch [27,28,29] among others, have also reported a similar trend. The maximum density of 4844 Individuals/L in Ganga River at the site in January, a similar trend was observed by Magar [30].…”
Section: Resultssupporting
confidence: 60%
“…Even with arsenic, many large-scale changes such as the formulation of tube well regulations need to take place at a state policy level (Chakraborti et al, 2013). Infrastructural policy suggestions related to dam construction and maintenance (e.g., Srivastava et al, 2020) are also the domain of state-level planners. This view of planning is perhaps slightly slanted, as it ignores the role that intermediary nongovernmental groups may have in policy formation.…”
Section: Lead Paints Frommentioning
confidence: 99%